Evaluation of the child-friendly school program based on the “5s” culture at Ngupasan Elementary School, Yogyakarta: evaluative research using the CIPP model - Martaningsih, Sri Tutur; Nur Fadhilah, Siti (Universitas Ahmad Dahlan, 2025)
Bullying cases in elementary schools still occur frequently, threatening students' sense of security and learning comfort. Child-friendly schools (CFS) play an important role in overcoming violence in schools, but their implementation requires commitment from various parties. This study aims to evaluate the implementation of the CFS program based on the